PENGARUH MEDIA SOSIAL TERHADAP KESEHATAN MENTAL REMAJA DI DESA NOTOGIWANG - putri, antika; Adinugraha, Hendri Hermawan; Anas, Ahmad (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This analysis is a qualitative approach to literature analysis. The data used in this study came from various academic scientific journals relevant to the research topic. The data analysis method used is the analysis of the literature used in the research. The purpose of this research is to find out the impact of social media and the negative impact of watching pornographic media. Social media is a type of internet media that allows users to easily participate in conversations, exchange ideas, and create virtual worlds. Social media has captivated the world in recent years. It is not surprising that the dangers to adolescent mental health from online exploitation of adolescent habits and behaviors have been threatening for a long time. The negative effect of social media is dehumanisation where one views people less humanly or considers them not human equals, then indirectly distances those who are close. Teenagers have a high curiosity about things they don’t know or things that are interesting and unique, so social media is very helpful for teenagers to find things they don’t know easily. On the other hand, high curiosity in teenagers can have a negative impact. For example, curiosity or interest in things about pornography because if you see something like that once, teenagers will feel curious and explore everything, and they become addicted to pornographic media. Adolescents who are addicted to pornography will be very detrimental to themselves because the effect of watching porn videos is very bad, namely damaging brain function and affecting adolescent mentality.